Antibacterial potential of the endophyte Phyllosticta fallopiae from wild tomato (Solanum pimpinellifolium) - ANINDITA SARMA; PINKY RANI BISWAS; KUMANAND TAYUNG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sarma A, Biswas PR, Tayung K. 2025. Antibacterial potential of the endophyte Phyllosticta fallopiae from wild tomato (Solanum pimpinellifolium). Biodiversitas 26: 4180-4192. The growing threat of antimicrobial resistance has necessitated the exploration for undiscovered novel antimicrobials from natural sources. Solanum pimpinellifolium, a wild relative of cultivated tomato is known for its built-in resistance to a variety of pests and pathogens. Literature studies indicated that such plants are colonized by distinct endophytic microbes that produce secondary metabolites of multiple applications. A total of 205 endophytic fungi were isolated from healthy leaf tissue of S. pimpinellifolium and five most dominant isolates were determined for antibacterial activity against eight clinically significant human pathogens using agar well diffusion method. The most potent isolate was identified at molecular level via ITS sequencing. Minimum Inhibitory Concentration (MIC) was determined using broth microdilution, and time-kill kinetics were performed to evaluate bactericidal effect. The extract was further analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) to identify active metabolites. The metabolite obtained from Phyllosticta fallopiae SPK5 (GenBank accession no. OR770585) was the most effective and showed the highest antibacterial activity against Enterococcus faecalis (25.67±0.58 mm), Bacillus anthracis (23.67±2.08 mm) and Staphylococcus aureus (21.00±1.00 mm). The extract showed promising Minimum Inhibitory Concentrations (MICs) of 15.62 µg/mL against Enterococcus faecalis and reduction in viable cell count in 12 h. Gas Chromatography-Mass Spectrometry (GC-MS) analysis of the potent extract revealed presence of seven major compounds including fatty acids, ketones and heterocycles such as Pyrrolo[1,2-a] pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl), octadecanoic acid, and 1-nonadecene, which are reported to have bioactive properties. These findings highlight the potential of wild tomato-associated endophytic fungi as a promising source of novel antimicrobial compounds, with possible applications in pharmaceutical development and management of multidrug-resistant pathogens.